Thermally stable Cu3Sn/Cu composite joint for high-temperature power device. (1st January 2016) - Liu, Xiangdong; He, Siliang; Nishikawa, Hiroshi
Graphical abstract: Abstract: This paper describes a novel transient liquid phase sinter (TLPS) bonding that utilizes Sn-coated micro-sized Cu particles for high-temperature power device packaging. When used as die attach materials for Cu–Cu bonding, a thermally stable joint comprising a Cu3 Sn intermetallic compounds (IMCs) with a dispersion of ductile Cu particles was obtained after bonding at 300 °C for 30 s, and a shear strength equivalent to that of conventional Pb–5Sn solder could be achieved. After isothermal aging at 300 °C for 200 h, the shear strength and microstructure of the bonding joints were almost unchanged.